Implementasi Akuntansi Syariah pada Sistem Bagi Hasil Pembiayaan Mudharabah dalam Praktik Keuangan Modern - Natria Aminarti; Rayyan Firdaus (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Mudharabah financing is a form of cooperation between shahibul mal (capital owner) who provides all the capital to mudharib (the manager). The profit sharing used in mudharabah financing, in this case there are two parties who make a business agreement, then the results of the business carried out by both parties or one of the parties, will be divided according to the portion of each party to the agreement. The purpose of this study is to determine the implementation of the profit-sharing system of mudharabah financing used to develop businesses in today's modern era. The research method used is literature review through literature study to collect data and research information by collecting materials from journals and scientific articles on mudharabah financing with profit sharing system. From the results of this study, the number of business actors in today's modern era, with the high need for small business capital, especially street vendors who at the same time find it difficult to fulfill the procedures for obtaining funding in the banking sector, this is a great opportunity for Sharia Financial Institutions (LKS) such as Baitul Mal wa Tamwil (BMT) to provide a forum for street vendors (mudharib) by issuing Mudharabah financing with the aim of improving the performance and income of a Micro, Small and Medium Enterprises (UMKM). So that mudharabah can play a role in sharia-based economic development and the growth of modern industrial society.